2008
DOI: 10.1111/j.1462-2920.2008.01673.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche partitioning in the picoplanktonic green alga Micromonas pusilla: evidence from environmental surveys using phylogenetic probes

Abstract: Very few studies have analysed the niches of pelagic protist in details. This is because for most protists, both an accurate species definition and methods for routine detection and quantification of cells are lacking. The morphospecies Micromonas pusilla, a marine unicellular green alga, is the most ubiquitous and cosmopolitan picoeukaryote described to date. This species comprises several independent genetic lineages or clades, which are not currently distinguishable based on comparison of their morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 33 publications
9
92
2
Order By: Relevance
“…Picoplanktonic chlorophytes cells (o3 mm) were represented almost exclusively by the Prasinophyceae Micromonas pusilla. The great abundance of Micromonas is consistent with previous estimation of picoplankton composition in the Mediterranean Sea including Blanes Bay (Foulon et al, 2008) but also in other oceanic regions (for example, Not et al, 2007;2004). Our results also revealed the existence of marked changes in the abundance of some nano-PFs (3-20 mm) along the year (cryptophytes and chlorophytes dominated at the end of winter, pigmented dinoflagellates increased in summer, and at the beginning of winter all groups increased significantly), whereas haptophytes were present all year-round always at a significant number without major fluctuations (Figure 2).…”
Section: Pico-and Nanophytoplankton Compositionsupporting
confidence: 78%
“…Picoplanktonic chlorophytes cells (o3 mm) were represented almost exclusively by the Prasinophyceae Micromonas pusilla. The great abundance of Micromonas is consistent with previous estimation of picoplankton composition in the Mediterranean Sea including Blanes Bay (Foulon et al, 2008) but also in other oceanic regions (for example, Not et al, 2007;2004). Our results also revealed the existence of marked changes in the abundance of some nano-PFs (3-20 mm) along the year (cryptophytes and chlorophytes dominated at the end of winter, pigmented dinoflagellates increased in summer, and at the beginning of winter all groups increased significantly), whereas haptophytes were present all year-round always at a significant number without major fluctuations (Figure 2).…”
Section: Pico-and Nanophytoplankton Compositionsupporting
confidence: 78%
“…Filters were incubated twice at 55 1C for 20 min in TNT buffer and then dried at room temperature. Cells were counterstained with propidium iodide (final concentration 10 mg ml À1 ) (Foulon et al, 2008) to visualize the nuclei. This allowed verification of labelling eukaryotic cells.…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenies based on the 18S rDNA showed that Micromonas and Ostreococcus are divided in several clades corresponding to different ecotypes and probably different species (see below) Šlapeta et al, 2006). This has been shown on the basis of physiological properties Cardol et al, 2008), geographical origin (Foulon et al, 2008), and niche partitioning (Demir-Hilton et al, 2011) of the strains/ecotypes. For example, "low light" and "high light" ecotypes have been described in Ostreococcus, corresponding to different clades .…”
Section: B Ecology and Molecular Evolution Of Oceanic Picoplanktonicmentioning
confidence: 99%